PENGARUH MEDIA PEMBELAJARAN EDUCANDY TERHADAP HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN MATEMATIKA DI SD NEGERI 141 PALEMBANG - Frizka Amelia; Ramanata Disurya; Tanzimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine how the influence of educandy learning media on the learning outcomes of fourth grade students in mathematics at SD Negeri 141 Palembang. The sample of this study was two classes selected by random sampling, namely students of class IV A and IV B at SD Negeri 141 Palembang. This study uses an experimental research method. Data collection methods using tests and documentation. With a posttest-only control design. The research data analysis method uses an independent sample t-test. The results show an average posttest of the experimental class of 85.00% and the control class of 67.77%. These results can be seen to state that learning outcomes and significant on the influence of educandy learning media using SPSS version 25 show that using the independent sample t-test obtained sig (2-tailed) <0.05 or 0.001 <0.05. And ttable = 0.2706 with a tcount value = 3.332 which shows that tcount> ttable. This is in accordance with the criteria for hypothesis testing that if tcount > ttable then H0 is rejected and Ha is accepted. Hypothesis testing proves that there is an influence of educandy learning media on the learning outcomes of grade IV students in mathematics at SD Negeri 141 Palembang.